A CORPUS ANALYSIS OF LEXICAL SOPHISTICATION IN LLT JOURNAL: A JOURNAL ON LANGUAGE AND LANGUAGE TEACHING - Monica Vinny Kusumaningrum; Priyatno Ardi (ELTR Journal, 2020)
This research focused on the description of lexical sophistication in LLT Journal: A Journal on Language and Language Teaching. To obtain the description of lexical sophistication in LLT Journal: A Journal on Language and Language Teaching, the researcher used a corpus software called Tool for the Automatic Analysis of Lexical Sophistication (TAALES). Sixty-six articles published in 2016, 2017 and 2018 were used as the data of this study. There were five descriptions of lexical sophistication in LLT Journal: A Journal on Language and Language Teaching, namely word frequency, word range, n-gram, academic list and word information. The word frequency (87%) showed the good amount of percentage in the articles. Word range (87%) showed the use of words in the articles were delivered properly. N-gram (35%) showed the sign of low lexical sophistication scores. Academic list (15%) showed low lexical sophistication scores. Word information (60%) showed high lexical sophistication scores. The percentage of each description of lexical sophistication showed that the academic list gained the lowest percentage among the other descriptions of lexical sophistication. It can be inferred that the academic list aspect in LLT Journal: A Journal on Language and Language Teaching needs to be upgraded.